Currency compositions of international reserves and the euro crisis - Falk Hendrik Laser; Jan Weidner (Technische Universität Darmstadt, Department of Law and Economics, 2020)
During recent years, central banks have increased the levels of their international reserves at an unprecedented pace. In this paper, we introduce new country-specific reserve data and examine determinants of the composition of international reserves. Using a dataset of 36 countries (and the euro area) for the years from 1996 to 2016, we identify currency pegs and trade patterns as determinants of currency compositions. Our results emphasize the importance of transaction motives for the composition of currency reserves. The euro crisis appears to have been a setback for the euro, which temporarily seemed to challenge the US dollar as the most important international reserve currency and potentially impacted the determination of international reserve compositions.
urn:nbn:de:tuda-tuprints-114711
Keywords: E58; F31; G01; 330; International reserves; central banks; euro crisis